Character and High Risk Behaviour of Drug Addicts for Spreading Hepatitis B and HIV Infection in a Selected Area of Dhaka City - Hakim, M; Ahmad, M; Naher, S; Ali, M; Ahmed, MU (Journal of Armed Forces Medical College, Bangladesh, 2014)
Introduction: The number of drug abusers is increasing in an alarming state in Bangladesh and they are identified as high risk group for developing Hepatitis B and HIV. Objectives: The aim of this study was to find out various information about drug addicts and their behavioural pattern which can guide the future developmental strategies and planning for reduction of spreading hepatitis B and HIV among the vulnerable population. Methods: This descriptive type of cross sectional study was performed during July 2006 to June 2007 in three different drug addiction treatment clinic in Uttara, Dhaka on high risk behaviour of drug addicts . A total 194 Drug addicts were interviewed individually by using a structured questionnaire. The questionnaire was filled up by the author during interview. All the data were checked and edited after collection on the spot. Compilation and subsequent tabulation were done manually. Simple technique of data analysis for percentage, average, standard deviations etc. were done with scientific calculator and using SPSS 11. Results: Out of 194 cases 180 (92.78%) were male and 114(58.76%) were unmarried. Most of them 118(60.82%) were within the age group of 20 to 29 years. They have an average family income of 12456.39 Taka per month. Most of the addicts 73(37.63%) were students. Average family size of drug addicts were 6.73 and majority of them 148(76.29%) resided with parents. Only 16(8.24%) drug addicts expressed quarrelsome relationship among their parents and 21(10.83%) stated a bad relationship with other family members. Of them 86(44.33%) started to have taking drug at an age range between 20 to 29 years and most of them 156(80.41%) used poly drug. Heroin 161(82.99%) ranked top as abused drug. Most of them 143(73.71%) were influenced by their friends for initiation of drug addiction. The average daily expense for drug was 191.13 Taka per day and most of them 142(73.19%) had frequency of drug abuse more than once daily. Only 20(10.31%) were found as Intravenous Drug Users (IDU); 16(80%) of the IDUs shared same syringe/needle. Among all the addicts 6(3.09%) were professional blood donor and among the IDU 4(20%) were professional blood donors. 139(71.65%) had history of sex without condom. 82(42.27%) were unaware about high risk behaviour due to lack of adequate knowledge. 185(95.36%) used to procure drug from black market. 5(25%) of IDU and 2(1.15%) of non IDU were found to be Hepatitis B positive though no HIV positive case was found. Conclusion: Wide spread motivation of the drug addicts and nationwide publicity regarding the ill effects of their high risk behaviour are needed to combat the spread of Hepatitis B/ HIV. DOI: http://dx.doi.org/10.3329/jafmc.v9i1.18723 Journal of Armed Forces Medical College Bangladesh Vol.9(1) 2013: 35-42